1988
DOI: 10.1002/1520-6807(198807)25:3<217::aid-pits2310250302>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A global approach for the interpretation of the kinetic school drawing (KSD): A quick scoring sheet, reference guide, and rating scale

Abstract: This paper presents a globally oriented scoring sheet, reference guide, and rating scale for facilitating clinical hypotheses from children's Kinetic School Drawings (KSDs) and further empirical evaluations of the KSD technique. The paper also provides information regarding the construction of these instruments, along with some preliminary findings in terms of the procedures' reliability and discriminant validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The Kinetic School Drawing test (Betts, ; Thompson Prout & Phillips, ; Wasserman, ) was used to measure the children's perception of teacher power in the context of school. This test reveals children's perceptions of teachers in the school setting (Andrews & Janzen, ; Prout & Celmer, ) and is a parallel assessment to the Kinetic Family Drawing test (Knoff & Prout, ). Specifically, in the drawing test, each child was asked to “Draw a school picture, and include yourself and your teacher in the picture”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kinetic School Drawing test (Betts, ; Thompson Prout & Phillips, ; Wasserman, ) was used to measure the children's perception of teacher power in the context of school. This test reveals children's perceptions of teachers in the school setting (Andrews & Janzen, ; Prout & Celmer, ) and is a parallel assessment to the Kinetic Family Drawing test (Knoff & Prout, ). Specifically, in the drawing test, each child was asked to “Draw a school picture, and include yourself and your teacher in the picture”.…”
Section: Methodsmentioning
confidence: 99%
“…Based on related studies (Andrews & Janzen, ; Charafeddine et al, ; Murphy et al, ; Prout & Celmer, ; Thompson Prout & Phillips, ; Thomsen et al, ), the score for teacher power was calculated by dividing the height of the teacher by the height of the child in the drawing. The children could use the nonverbal spatial cues to perceive and represent the perception of power (Charafeddine et al, ; Schubert, Waldzus, & Giessner, ), and relative height could represent the perception of relative power between the teacher and the child (Andrews & Janzen, ; Thomsen et al, ). Therefore, the height of the teacher relative to that of the child in the children's drawings was adopted as the score for the children's perception of teacher power, and higher scores reflected the higher levels of teacher power relative to the child.…”
Section: Methodsmentioning
confidence: 99%
“…The heights of and distances between individuals depicted in the drawings were recorded, with measurements logged in centimeters and rounded to the nearest tenth. These measurements were relevant because child drawing interpretation experts have found that (a) children tend to draw taller figures to represent the confidence and stability of those characters, and (b) children often place characters in closer proximity to indicate positive social bonds (Andrews & Janzen, 1988;Cherney et al, 2006). Character affect (smiling, frowning, or flat) was also recorded as well as whether the characters portrayed had arms and hands, the absence of which potentially indicates timidity or lack of agency (Koppitz, 1968;Thomas & Jolley, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Great interest among researchers appeared for the kinetic approach also to school drawing because it seemed to provide a richer source of data than did static drawings (Andrews & Janzen, 1988;Armstrong, 2004;Prout & Celmer, 1984). School and class drawings have been used to document gifted students' perceptions of school life as they provide nonverbal documentation of gifted students' perceptions of their current school experiences.…”
Section: Drawings As a Technique To 'Assess' The Gifted Students' Needsmentioning
confidence: 99%